Prospecção geológica e geofísica com ênfase em formações ferríferas na faixa meridional do Quadrilátero Ferrífero do Supergrupo Minas Indiviso - Inachvili, Irakli [UNESP] (2014)
The works of geological research or academic texts along the southern range of the quadrilátero ferrífero of Minas Supergroup Indiviso leaves certain grace period for a region as yet little exploited economically in relation to deposits of iron formations that are starting to become viable. This study correlated magnetic anomalies interpreted by geophysical aerial survey (magnetometry and gamma spectrometry) with the lithologies mapped undivided band Super Group Mines, with emphasis on iron formations associated, thus, good horizons guide to geological exploration. Field data collected over the recognition and geological mapping were the basis for confirmation and validation of geological and geophysical interpretations, confirming rock types that generate signatures (anomalies) magnetic, and prospected in this study region describes field a tectonic evolution, metamorphic distinct structural and the quadrilátero ferrífero